If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -10 = 2x + 2 Reorder the terms: -10 + 6x = 2x + 2 Reorder the terms: -10 + 6x = 2 + 2x Solving -10 + 6x = 2 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -10 + 6x + -2x = 2 + 2x + -2x Combine like terms: 6x + -2x = 4x -10 + 4x = 2 + 2x + -2x Combine like terms: 2x + -2x = 0 -10 + 4x = 2 + 0 -10 + 4x = 2 Add '10' to each side of the equation. -10 + 10 + 4x = 2 + 10 Combine like terms: -10 + 10 = 0 0 + 4x = 2 + 10 4x = 2 + 10 Combine like terms: 2 + 10 = 12 4x = 12 Divide each side by '4'. x = 3 Simplifying x = 3
| w^3+4w-96=0 | | 10(h-1)+18=7(h+3-1) | | 8=4.2r-7+1.8r | | x+5.2=6.7 | | 0,7*15= | | -3(x+8)-41=7-57 | | 6p^6-11p^3r+4r^2=0 | | 4(y+2)+8=7y-3 | | t^2-7ty-18y^2=0 | | -3x+28=x^2 | | v^2-2vz-80z^2=0 | | t^2-3tf-10f^2=0 | | 12s^2+43s+35=0 | | 2x.2= | | 21a^2+22a-8=0 | | r^4+81r^2+80=0 | | 6x^3-18x^2-2040x=0 | | 4b^2-22b+10=0 | | 9s^2+6s+1=0 | | 8x=4(6x+28) | | 19=5n+7-3n | | -7w-24=-5w-30 | | e^5x=24 | | e^5x=4 | | 5v^2+23v+24=0 | | -8x^2-40x+48=0 | | -8b+4+6b=-3b+9 | | xx+9x=-20 | | -6x+18=-4x+4 | | 6xx+18x=0 | | 6x+1y=163.5 | | 3x+1y=156.75 |